Identifying growth opportunities in the Southern African Development Community through regional value chains: The case of the animal feed to poultry value chain - Phumzile Ncube; Simon Roberts; Tatenda Zengeni; Paul C. Samboko (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper considers findings of studies analysing the development of a regional animal feed to poultry value chain in southern Africa (Botswana, South Africa, Zambia, Zimbabwe). The southern African regional poultry value chain is underdeveloped, although important changes include investments by South Africa-based multinational firms and strong growth in Zambia. Building on this growth requires coherent trade and industrial policies supporting investments across countries and practical measures to reduce barriers to intra-regional trade and transport costs. The potential to develop a regional poultry value chain is substantial, considering that the South African deep-sea trade deficit in poultry is larger in size than the Zambian industry.
Keywords: L66; O55; Q13; O25; 330; value chain; southern Africa; poultry; trade policies; industrial policies; case study